Asynchronous Message Transmission Technique for Latency Requirements in Time Critical Ship-borne System - Shrivastava, N. P.; Shrotriya, S. (Defence Science Journal, 2016)
A solution to data ageing requirements in time critical ship system like fire control system is presented. In an operational sea borne platform, navigation requirements for the onboard systems are fulfilled by ring laser gyro-based inertial navigation system. For critical systems like fire control system, navigational data must be delivered in real time without any delay. However due to delay occurring in processing of raw information and transmission of data on interface bus some latency is introduced. Algorithm for an asynchronous message transmission technique from inertial navigation system to user system to meet its latency requirements is discussed. Latency requirement is achieved by sending a separate message with the time stamp for the instance the first byte of 100 Hz attitude data is received at the processing computer of navigation system.